CLIL and Comprehensive Sexual Education: A Case of Innovation From Argentina - Darío Luis Banegas; Cristina Lauze (Profile: Issues in Teachers' Professional Development)
Social issues are believed to enrich English language teaching with meaningful topics. In this article we describe and reflect on an innovative practice which combined content and language integrated learning with comprehensive sexual education at a state secondary school in Argentina. By law, comprehensive sexual education must be included across the Argentinian curriculum and English language learning cannot be the exception. Therefore, we designed and implemented a collaborative-driven innovation that allowed learners to learn English and comprehensive sexual education with a focus on authentic materials, purposes, and tasks. The innovation was developed over a month and it involved learners delivering presentations on comprehensive sexual education topics. Reflections on the effect of the innovation and possible future directions are included.